Bi(Me)O3-PbTiO3 high TC piezoelectric multilayers. (1st September 2013) - Cumming, D J; Sebastian, T; Sterianou, I; Rödel, J; Reaney, I M
Abstract : Multilayer structures based on the composition 0·52(0·35Bi(Mg1/2 Ti1/2 )O3 -0·3BiFeO3 -0·35BiScO3 )-0·48PbTiO3 (BMFS-PT) have been fabricated with large piezoelectric activity and high T C . Reaction with Pt internal electrodes during cofiring leads to a decrease in T C and softening of the ferroelectric response, consistent with donor doping. However, this effect is minimised by extending binder burnout times up to 4 h and in samples with thicker active layers (∼100 μm). Multilayer actuators based on BMTFS-PT should therefore increase the operating temperature to <100°C above PZT structures with equivalent piezoelectric activity.